Knowledge creates markets: The influence of entrepreneurial support and patent rights on academic entrepreneurship - Dirk Czarnitzki; Thorsten Doherr; Katrin Hussinger; Paula Schliessler; Andrew A. Toole (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We use an exogenous change in German Federal law to examine how entrepreneurial support and the ownership of patent rights influence academic entrepreneurship. In 2002, the German Federal Government enacted a major reform called Knowledge Creates Markets that set up new infrastructure to facilitate university-industry technology transfer and shifted the ownership of patent rights from university researchers to their universities. Based on a novel researcher-level panel database that includes a control group not affected by the policy change, we find no evidence that the new infrastructure resulted in an increase in start-up companies by university researchers. The shift in patent rights may have strengthened the relationship between patents on university-discovered inventions and university start-ups; however, it substantially decreased the volume of patents with the largest decrease taking place in faculty-firm patenting relationships.
urn:nbn:de:bsz:180-madoc-410742
Keywords: O34; O38; 330; intellectual property; patents; technology transfer; policy evaluation